Redburn. His First Voyage : Being the Sailor Boy Confessions and Reminiscences of the Son-Of-A-Gentleman in the Merchant Navy - Melville, Herman, 1819-1891 (Salt Lake City, UT : Project Gutenberg, 2005)
"Redburn. His First Voyage" by Herman Melville is a semi-autobiographical novel published in 1849. It follows young Wellingborough Redburn, a gentleman's son who signs onto a merchant ship bound for Liverpool. Expecting respect, he instead faces brutal treatment as the lowest-ranking sailor aboard. He encounters tyrannical crewmates, witnesses devastating poverty in Liverpool's streets, and befriends a mysterious dandy whose secrets unfold during their return voyage. The novel chronicles a youth's harsh awakening to life's cruelties at sea and ashore. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Redburn
Release date is 2005-05-01
Project Gutenberg volunteers and Blackmask Online
Keywords: Sea stories; Autobiographical fiction; Bildungsromans; Young men -- Fiction; Americans -- England -- Fiction; Sailors -- Fiction; Seafaring life -- Fiction; Merchant mariners -- Fiction; Liverpool (England) -- Fiction